BSP-based Swarm Behaviour Implementation for Underwater Multiagent Environmental Low-frequency Sensing. Issue 21 (2019) - Bonsignorio, Fabio; Zereik, Enrica; Caccia, Massimo
Abstract: The environmental chemical conditions - in terms of substances with positive and negative impacts on the sustainability of local ecological networks - of confined environments with weak currents change over time in probabilistically predictable ways. We are developing a reproducible and measurable approach to the deployment of complex adaptive networks of underwater gliders, ROVs and fixed or mobile sensors deployed on the sea floor. The approach exploits Voronoi maps, multisensory fusion of different kind of chemical and non chemical sensors framed by a multi agent Belief Space Planning methodology. In this paper we report the early results of the study of the swarm behaviour implementation of a set of gliders or ROVs that can work autonomously (in the case of ROVs semi-autonomously or autonomously for limited time frames). In particular we describe how we were able to implement a swarm behaviour by means of a novel multiagent implementation of a BSP control scheme that we have already studied in the context of the Project CADDY (7th Framework Program (2014)).